Reprodutibilidade e validade do incremental shuttle walking test em indivíduos adultos asmáticos - Labadessa, Ivana Gonçalves (2017)
The present thesis has a result two studies in which the aims were: Study I – to evaluate the reliability test retest of the incremental Shuttle Walk Test (ISWT) for the walked distance in ISWT (ISWTD), cardiorespiratory responses, metabolic responses and effort perception in young adults with asthma control. Study II – to evaluate the reliability and validity of the ISWT in detecting exercise-induced bronchospasm (EIB) in young adults with asthma control. Thirty-four asthmatic subjects participated in this study, and for the second study, 32 asthmatics participated. On the first day, a pre-and post-bronchodilator (BD) lung function test was performed and the first ISWT for familiarization. On the second day, an incremental cardiopulmonary exercise test (ICPET) was performed and after a 48-hour interval on the third day a constant cardiopulmonary exercise test (CCPET) was performed, both were performed with temperature and humidity of the controlled air according to recommendations for cardiopulmonary exercise (CPET). On the fourth day, the second ISWT (ISWT-2) was performed in a flat and covered corridor and after a minimum interval of 48 hours and a maximum of seven days on the fifth day the third ISWT (ISWT-3) were performed under the same conditions and both were conducted by the same evaluator. In addition, a portable telemetry system was used to capture the breath-to-breath ergospirometry variables. This system was also used to perform the pulmonary function test using a facial mask and forced vital capacity maneuvers (FVC) were also performed to obtain forced expiratory volume values in the first second (FEV1), with three reproducible maneuvers before Tests, and a maneuver at 5', 10', 15', 20' and 30' minutes after the tests, except for the ICPET, in order to evaluate the occurrence of EIB. The values of the intraclass correlation coefficient (ICC) were higher than 0.75 (p <0.001) for ISWTD, the absolute oxygen uptake (ml/min) and corrected by body mass (ml / kg / min) (VO2), carbon dioxide (ml/min) and minute ventilation (l/min) (VE). The Bland-Altman plots presented mean error and limits of agreement within acceptable limits of variation with the exception sensation of dyspnea (SD), which presented a mean error far from zero and high agreement limits, showing that SD was higher in the third ISWT compared to the second ISWT. Reliability analysis for EIB detection was weak (k=0.24; p>0.169). For the validity analyzes we found a weak value between ISWT-2 and CCPET (k=0.059; p>0.618) and a moderate value between ISWT-3 and CCPET (0.46; p<0.002). There was also a significant moderate association between ISWT-3 and CCPET (r=0.51; p<0.01). Regarding the physiological responses, the ventilation time during the tests above 40% of the maximum voluntary ventilation (MVV) was lower in ISWT-2 and ISWT-3 than in CCPET (p=0.000; p=0.000), a significant difference was found for the moment when an VE > 40% of the MVV was reached in the positive EIB group (p=0.000; p=0.000) and negative EIB (p=0.044; p=0.028) between the ISWT-2 vs CCPET and ISWT-3 vs CCPET, respectively, in other words, asthmatic individuals took longer to achieve ventilatory demand in ISWT-2 and ISWT-3 than in CCPET and the respiratory rate (RR) was higher in the ISWT-3 compared to the CCPET for the positive EIB group (p=0.010).